Study of Verbal Bullying in Early Adolescents (Case Study of Pallangga 5 Junior High School and Sungguminasa 3 Junior High School) (Medico Legal Update, 2021)
Bullying can take many forms, one of which is verbal bullying in the form of reproach, slander, cruelcriticism, personal or racial insults. This study aims to examine the incidence of verbal bullying that occursin early adolescents at Pallangga 5 Junior High School and Sungguminasa 3 Junior High School, GowaRegency. This research uses a qualitative case study approach. Data was obtained through Focus GroupDiscussion (FGD), in-depth interviews with 59 informants and document review. Content analysis is usedto identify topics or categories in the data. The results showed that the forms of verbal bullying varied,ranging from harassing, threatening, using verbal abuse by making fun of parents and the name of thevictim. Therefore, schools should intensify the activities of the ambassador team so that verbal bullying canbe minimized and teachers need to add insight into verbal bullying.